2015
DOI: 10.1002/hep.27723
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effect of antiviral therapy on disease course after decompensation in patients with hepatitis B virus–related cirrhosis

Abstract: The effect of viral suppression on long-term disease outcome after decompensation in patients with hepatitis B virus (HBV)-related cirrhosis has not been established. The aim of this study was to determine the long-term effect of antiviral therapy (AVT) in patients with HBV-related decompensated cirrhosis. This was a multicenter, prospective, inception cohort study of 707 patients who presented with first-onset decompensated complications, including 284 untreated and 423 antiviral-treated patients (58 previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
116
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(122 citation statements)
references
References 24 publications
3
116
0
3
Order By: Relevance
“…1,57 There is strong evidence that antiviral therapy significantly modifies the natural history of decompensated cirrhosis, improving liver function and increasing survival. 57,58,148 Meta-analyses demonstrated an overall and transplant-free survival in NA treated patients of more than 80%, respectively. 58,59 Approximately 35% of treated patients can be delisted for liver transplantation, and an improvement of Child-Pugh Score P2 observed in at least 40-50%.…”
Section: Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…1,57 There is strong evidence that antiviral therapy significantly modifies the natural history of decompensated cirrhosis, improving liver function and increasing survival. 57,58,148 Meta-analyses demonstrated an overall and transplant-free survival in NA treated patients of more than 80%, respectively. 58,59 Approximately 35% of treated patients can be delisted for liver transplantation, and an improvement of Child-Pugh Score P2 observed in at least 40-50%.…”
Section: Recommendationsmentioning
confidence: 99%
“…Patients with early treatment initiation had better clinical outcomes than those with delayed treatment. 148 High baseline Child-Pugh or MELD scores are predictors of poor survival meaning that the disease may have progressed beyond the point of no return. 58,[148][149][150] In contrast, an improvement in MELD or Child-Pugh score early on-treatment is highly predictive of transplant-free survival.…”
Section: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although successful treatment outcomes in HCV induced cirrhotics resulted in the significant prevention of HCC [39] , it is not yet clear whether DAA treatment for decompensated HCV-LC lowers the incidence of HCC. Actually, despite clinical improvement, the occurrence of HCC was not significantly suppressed by NA treatment for decompensated HBV-LC [35] . However, given the difference of pathogenesis between HBV and HCV, in that one virus integrates into the genome and the other does not, the two infections might not always respond in a similar fashion.…”
Section: Expectations and Concerns Of Daa Treatment For Decompensatedmentioning
confidence: 96%
“…Jang et al [35] reported the long-term effect of the NAs in patients with decompensated HBV-LC. They followed 284 untreated patients and 423 treated with NAs for more than 7 years and found that transplant-free survival was significantly improved in those treated with NAs (59.7% vs 46.0%).…”
Section: Expectations and Concerns Of Daa Treatment For Decompensatedmentioning
confidence: 99%